THE ENCOUNTER BETWEEN CUSTOM AND RELIGION IN RURAL COMMUNITIES: TENGGER TRIBE WEDDING RITUALS - Amin Tohari; Lailiyatul Azizah (Harmoni, 2022)
Dialogue between local culture and Islam is the main feature of peripheral Indonesian Islam. In rural sociology, a clash will occur when the two go hand in hand in social interaction. The Tenggerese people in East Java, as rural residents, face the dilemma of clashing customs and religion through traditional marriages. This article seeks to answer how the traditional wedding ritual procession as a local identity also applies to the Muslim minority in Tengger, and how the two (custom and religion) negotiate both so that a balanced meeting point is reached. Using a qualitative approach and case study methods, data collection was done by interview and observation. The results that they have compromised by finding common ground, including the meeting of principles and essence between adat and religion, the transition from endogamy to exogamy, and the division of roles during the traditional wedding procession. This article provides a novelty that the meeting of the two resulted in a new color in religious moderation in Indonesia that is not found elsewhere and with a different pattern as the distinctive identity of the Tengger rural community.